Processing of Histopathological Data - GERARD-MARCHANT, R.; WOLFF-TERROINE, M.; RENAUD, M.; AQARQ, M. (Methods of Information in Medicine, 1971)
A method is presented for processing data from the histopathological laboratory of a cancer hospital. Emphasis is laid on the ease of use, the connection of medical, administrative and financial data, and the strictness of control of patient’s identification number. The system can be used separately; it is also a module for a large integrated system covering all the activities of the hospital.
Keywords: EDP of Histopathological Data; Record Processing; Integrated Systems